How Nalco revitalized its quality process for R&D - Keiser, Bruce A. (Research management (Now: research technology management))
Bruce A. Keiser and Natalie R. Blake describe the steps Nalco Chemical Co. took to develop a quality improvement process that met the company's own needs.